Changing treatment strategy of cavernous sinus meningiomas: experience of a single institution - BAYRAKLI, FATİH (ELSEVIER SCIENCE INC, 2005)
Background: Oncological treatment of a neoplasm is more than surgical removal of the tumor. Probably, this truth is the reason for the ongoing discussion on cavernous sinus meningiomas in the last decade. Debate on optimal management of cavernous sinus meningiomas aims to compare the different treatment strategies: (a) radical surgical resection and (b) conservative surgical resection complemented with radiosurgical treatment. Materials and Methods: Natural history of the change in the management strategy of cavernous sinus meningiomas in our department before and after GK facility became available in 1997 allowed us to compare the 2 aforementioned strategies. Before installation of a Leksell GK unit at the hospital in 1997, the neurosurgical team at Marmara University Institute of Neurological Sciences and Faculty of Medicine (Istanbul, Turkey) treated patients with cavernous sinus meningioma using radical resection (radical strategy, group A, 10 patients). After 1997, the same neurosurgical team used understanding of surgical removal of the extracavernous sinus tumor component with GK irradiation of the intracavernous part (conservative strategy, group B, 12 patients). Another group of patients, who were treated with GK as a first-step treatment, was analyzed (GK group, group C, 26 patients). Results: At the end of the third year, more stable tumor volume control was achieved in groups B and C; after the second year, an incline in the tumor volume-time graph was detected. Group B resulted in less cranial nerverelated complications; a certain degree of improvement in cranial nerve deficits was observed. Conclusion: Comparing 2 different management strategies for cavernous sinus meningiomas in the same hospital setting using the same neurosurgical group, we conclude that extracavernous resection followed by GK is as effective as radical surgery. Considering cranial nerve complications and third-year tumor volume control achievement, conservative approach yielded better results. Longer follow-up with larger series is necessary. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: meningioma; radical resection; gamma knife irradiation; GAMMA-KNIFE RADIOSURGERY; GROWTH-FACTOR; FOLLOW-UP; MANAGEMENT; SURGERY; RECURRENCE; TUMORS; PROGRESSION; EXPRESSION; CHORDOMAS